2005
DOI: 10.1038/nature04213
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the short γ-ray burst GRB 050709

Abstract: Gamma-ray bursts (GRBs) fall into two classes: short-hard and long-soft bursts. The latter are now known to have X-ray and optical afterglows, to occur at cosmological distances in star-forming galaxies, and to be associated with the explosion of massive stars. In contrast, the distance scale, the energy scale and the progenitors of the short bursts have remained a mystery. Here we report the discovery of a short-hard burst whose accurate localization has led to follow-up observations that have identified the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
235
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(247 citation statements)
references
References 29 publications
9
235
0
3
Order By: Relevance
“…Although the two burst populations have different progenitors, the outflow that produces them must have a very high compactness in both cases, and may be driven by essentially the same mechanism (e.g., a MHD jet). The short GRBs have systematically higher peak energies than is implied by the Amati et al (2002) relation (Donaghy et al 2007), but so far only GRB 050709 has both a well-defined redshift and measured spectral peak energy (Fox et al 2005;Villasenor et al 2005).…”
Section: Implications For the E Pk -E Iso Relation Of Short Grbsmentioning
confidence: 76%
“…Although the two burst populations have different progenitors, the outflow that produces them must have a very high compactness in both cases, and may be driven by essentially the same mechanism (e.g., a MHD jet). The short GRBs have systematically higher peak energies than is implied by the Amati et al (2002) relation (Donaghy et al 2007), but so far only GRB 050709 has both a well-defined redshift and measured spectral peak energy (Fox et al 2005;Villasenor et al 2005).…”
Section: Implications For the E Pk -E Iso Relation Of Short Grbsmentioning
confidence: 76%
“…This situation has changed with the detection of X-ray afterglow from several short bursts by Swift (Gehrels et al 2005;Romano et al 2005) and by HETE II (Villasenor et al 2005). In some cases, optical (Covino et al 2005;Fox et al 2005;Bloom et al 2006;Price et al 2005;Jensen et al 2005;Hjorth et al 2005;Castro-Tiraldo et al 2005;Gal-Yam et al 2005b;Cobb et al 2005;Wiersema et al 2005) and radio (Cameron & Frail 2005;Berger 2005) afterglow was detected as well.…”
Section: Introductionmentioning
confidence: 99%
“…They noticed the existence of hybrid sources with an occasional, softer, prolonged emission lasting tenths of seconds in the gamma-ray energy band, following an initial spike-like emission comprising an otherwise short burst. The observations by Swift further infringed the short/long dichotomy in many ways: some short duration GRBs were observed to be followed by an X-ray afterglow (first GRB 050509B observed by Swift, see Gehrels et al 2005; and, two months later, GRB 050709 observed by HETE-2, see Villasenor et al 2005); some nearby long-duration GRBs were also observed to be not associated with SN (GRB 060614, Della Valle et al 2006;Fynbo et al 2006;Gal-Yam et al 2006;and GRB 060505, Xu et al 2009). …”
Section: Introductionmentioning
confidence: 99%